Mental health in adolescents of Delicias (trujillo - Perú) - Perales Cabrera, Alberto (2001)
OBJECTIVE: To examine the mental health of 12 to 18 year-old adolescent population. MATERIAL AND METHODS: A mental health household survey was carried out in a sample randomly selected from two areas of Las Delicias, District of Moche, Trujillo City, Peru: 32 subjects from Taquila (a rural area) and 43 from the North Zone (an area in process of urbanization). RESULTS: Problems related to substance abuse, mainly alcohol, were more predominant in Taquila while symptoms of distress and depression with lower family and social support were evident in the North Zone; the differences between the two subsamples were statistically significant. CONCLUSION: Stressors related to the described problems are probably immerse in the macrovariables associated to the urbanization process of that population.